The Role of Physical Activity on Spatial and Temporal Cognitive Processing in Young Women - Joaquín Castillo-Escamilla; María del Mar Salvador-Viñas; José Manuel Cimadevilla (Brain Sciences)
Background/Objectives: Physical activity (PA) has many benefits for both physical and cognitive health. It has also been related to improvements in memory and executive functions. However, its impact on time estimation remains less explored. Time is a key component of episodic memory, which also involves spatial components to give a full context to events. Given the clear evidence of the benefits of PA in spatial navigation and the anatomical overlap with temporal estimation through the hippocampus, the latter could be affected in a similar way. Therefore, this study aimed to check how PA can influence time processing and spatial memory. We wanted to check if PA influenced time and space with the same directionality. Methods: Forty-two (n = 42) female university students participated in this study, divided into a Sport (n = 25) or Sedentary (n = 17) Group depending on their participation in PA for a minimum of 3 h a week. They were addressed in two different cognitive capabilities. The first was time processing, measured by the Time Comparison Task, which controlled for several key aspects of time literature in its design. Moreover, we measured spatial navigation skills, using a well-proven virtual spatial navigation task, The Boxes Room. Accuracy and mean response times were registered per task. Results: Significant correlations were observed between spatial and temporal task performance. In addition, PA influenced spatial and time processing in a similar way, with the Sport Group outperforming the Sedentary Group in accuracy and response times for both tasks. Conclusions: These findings provide evidence that PA influences time processing similarly to its established effects on spatial memory, which could help developing sports programs that further enhance this skill.